(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Skin cancer is among the malignancies that spreads the quickest among the few kinds of cancer that are known to people. Melanoma is the absolute most horrendous and hazardous sort of skin cancer that normally shows up on the skin's surface prior to spreading deeper into the skin's layers. The most pervasive kind of cancer is liable for a critical number of passing’s every year. Most significant exploration works center around man-made intelligence subordinate computations, with not very many additionally tending to deep learning. Be that as it may, because of a couple of issues with dermo scopic picture getting, these computations can't give the most noteworthy conceivable level of explicitness and accuracy. Subsequently, the skin cancer detection and classification (SCDC) framework is executed in this paper utilizing multilevel feature extraction (MFE)- based artificial intelligence (man-made intelligence) with unsupervised learning (USL), which is alluded to as MFEUsLNet. At first, the gave skin pictures are pre-handled utilizing a two-sided channel, eliminating the Arti real factors' unsettling influence from the first pictures. Then, to separate the skin sore, a notable USL method called K-means clustering (KMC) is applied, which effectively recognizes the impacted skin injury. By then, low level, surface, and colour feature extraction are finished utilizing gray level co-occurrence matrix (GLCM) and redundant discrete wavelet transform (RDWT). At last, a recurrent neural network (RNN) classifier is utilized to rank the different types of skin cancer utilizing these stunned features. That's what the entertainments showed, regarding clinically discernible quality estimations, like classification precision, disposition, accuracy, investigate, F1-score, and mindfulness for ISIC-2020 dataset, the proposed MFEUsLNet model outflanks cutting edge SCDC techniques.